Financial Performance Analysis - Ariyo Bimo, Widhi; Nugraha; Sudrajat, Ajat; Hermawan, Harry (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This study aims to determine the financial performance of the UIKA Bogor Employee Cooperative, using a comparative qualitative research method to describe and compare as it is based on the results of the analysis of the financial statements of the UIKA Employee Cooperative, namely the balance sheet and income statement obtained from the period 2021 to the period 2022. Using indicators of liquidity ratios, solvency ratios, profitability ratios and activity ratios, direct observation, interviews, documentation, and library research are carried out. The Liquidity Ratio shows that the performance of the UIKA Employee Cooperative has the ability to pay off its debts that are due immediately, and has the ability to pay off its debts with the most current assets, the solvency ratio has a low risk, which means that the level of security of its funds is high, it has the ability to pay its long-term obligations well, it can be said to have a safe capital structure, the profitability ratio has an increase in profit from the previous year based on all activities carried out, there is an increase in profit based on own capital owned, and the activity ratio has an increase in accounts receivable turnover from the previous year, effective in managing its receivables, and effectively using its fixed assets in earning income